ASSESSMENT OF INNOVATION AND INVESTMENT SUPPORT SECURITY OF ENTERPRISES AND AGRARIAN SECTOR OF UKRAINE - Zhadko , K.S.; Nosova , T.I. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The article considers the assessment of investment support and as a derivative of innovative ensuring economic security both at the micro level – enterprises and at the macro level – of the agricultural sector as an industry of the Ukrainian economy. The assessment of investment and innovation support for the economic security of the agricultural sector in Ukraine involves the analysis of investment indicators in the areas of activity and resources of enterprises and the attraction of innovative technologies. As a result of investments in updating fixed assets, equipment, machinery and equipment, production technologies. Innovations and new technologies are derived from investments, the synergy of which ensures the economic security of the subjects of the agricultural sector of Ukraine. The structure and size of investments are analyzed, how they affect the innovative provision of economic security of the agricultural sector. It is proposed: ways to increase innovation and investment attractiveness in the agricultural sector, directions of state support and methodical aspects of strengthening economic security starting from enterprises and the agricultural sector of Ukraine as a whole.